Cognitive workload during verbal abstract reasoning in Parkinson's disease: a pilot study. (4th May 2021) - Moon, Sanghee; Kahya, Melike; Lyons, Kelly E.; Pahwa, Rajesh; Akinwuntan, Abiodun E.; Devos, Hannes
Abstract: Background: Pupillary response reflects cognitive workload during processing speed, working memory, and arithmetic tasks in Parkinson's disease (PD). Abstract reasoning, a higher-order cognitive function that relates different objects, events, or thoughts in a similar manner, may also be compromised in PD. The aim of this study was to compare pupillary response as a measure of cognitive workload while completing a verbal abstract reasoning test between patients with PD and age-matched controls. Methods: Nineteen non-demented individuals with PD (66.6 ± 8.9 years) and 10 healthy controls (65.3 ± 7.3 years) were recruited. A remote eye tracker recorded the pupillary response at 60 Hz, while the participants were performing the Similarities test of Wechsler Adult Intelligence Scale-IV. Outcome measures included pupillary response, evaluated by the Index of Cognitive Activity (ICA), and behavioral responses of the Similarities test. Results: The PD group (scaled scores = 8.9 ± 2.2) did not show impairment in behavioral performance on Similarities test compared with healthy controls (scaled scores = 8.8 ± 2.3; p = .91). However, the PD group (ICA = .32 ± .09) demonstrated significantly greater cognitive workload during the Similarities test compared to controls (ICA = .24 ± .08; p = .03). Conclusions: Non-demented individuals with PD exerted greater cognitive workload to complete a verbal abstract reasoning task despite similar behavioral performance compared to healthy controls. Clinical utilities of pupillary response to detect and monitor early impairment in higher-order executive function will be the subject of further study in the PD population.